Adult onset Best’s macular dystrophy (VMD2) with unilateral presentation - Kamat, Pradnya; Doshi, Pratik; Prabhudesai, Manasi; Prabhudesai, Srishti (Nepalese Journal of Ophthalmology, 2017)
Background: Vitelliform macular dystrophy is an autosomal-dominant disease and has two clinical variants: Best’s (VMD2) and adult onset vitelliform macular dystrophy (AOVMD). We report an atypical presentation of VMD2. Case: A 50-year-old male presented with history of blurring of vision in left eye since two year. On fundus examination, left eye revealed a single, circular, yellow-opaque egg yolk-like macular lesion with no other abnormality. Fundus examination of right eye was unremarkable. Fundus fluoresceine angiography showed blocked fluorescence in the area of lesion. EOG-Arden ratios were found to be severely reduced bilaterally. OCT left eye showed sub-retinal hyperreflective echo. Conclusion: The age of onset and presentation can be highly variable in VMD2 and the vitelliform phase of VMD2 in elderly can be confused for adult onset vitelliform macular dystrophy(AOVMD). However, Arden ratio <1.5 is diagnostic of VMD2.